Exploring nurse practitioners’ collaboration with general practitioners in Norwegian homecare services: a qualitative study - Lene Apeness Kjær; Mette Tøien; Linn Hege Førsund (Scandinavian Journal of Primary Health Care)
Objective Nurse practitioners (NPs) have recently been introduced in Norwegian homecare services. The NP role is still in an early implementation phase without standardized role descriptions. NPs are dependent on collaborating with general practitioners (GPs) in the care and treatment of patients. However, little is known about how NPs in Norway experience this collaboration. This study aims to explore how NPs working in homecare services describe their collaborative experiences with GPs, and what influence this collaboration.Design The study had a qualitative descriptive design, applying individual, semi structured interviews to generate data from five Norwegian nurse practitioners working in homecare services. Data were analyzed using systematic text condensation.Findings The NPs had varied experiences regarding the collaboration with GPs. NPs stated their role as unclear, lacking standards and job descriptions. The NPs experienced that some GPs were uncertain about the NPs competence, which inhibited collaboration and restricted the NPs utilization of their full capability.NPs experienced a higher degree of collaboration with GPs they knew, and they indicated that trust was the key to facilitate collaboration. The NPs also noted the challenges of establishing relationships with GPs due to the lack of formal meetings and the physical separation of their workplaces.Conclusion Interpersonal dynamics, organizational structures and systemic frameworks influenced the collaboration between GPs and NPs in homecare services. Trust was identified as an important prerequisite for collaboration.